2022
DOI: 10.1021/acsomega.1c04659
|View full text |Cite
|
Sign up to set email alerts
|

B-nor-methylene Colchicinoid PT-100 Selectively Induces Apoptosis in Multidrug-Resistant Human Cancer Cells via an Intrinsic Pathway in a Caspase-Independent Manner

Abstract: Colchicine, the main active alkaloid from Colchicum autumnale L., is a potent tubulin binder and represents an interesting lead structure for the development of potential anticancer chemotherapeutics. We report on the synthesis and investigation of potentially reactive colchicinoids and their surprising biological activities. In particular, the previously undescribed colchicinoid PT-100, a B-ring contracted 6-exo-methylene colchicinoid, exhibits extraordinarily high antiproliferative and apoptosis-inducing eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Based on the analysis of the protein-protein interaction network, the top 25 targets from 22-(4 py)-JA were related to NSCLC aggressiveness and found to participate in cancerassociated pathways. Apoptosis is a major mode of action of cancer therapies, and resistance to this programmed cell death facilitates long-lived cancer cells with an accumulation of gene mutations, contributing to uncontrolled cell growth, vascularization and tumor invasion [24,33]. We then focused on the apoptosis targets of 22-(4 py)-JA in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis of the protein-protein interaction network, the top 25 targets from 22-(4 py)-JA were related to NSCLC aggressiveness and found to participate in cancerassociated pathways. Apoptosis is a major mode of action of cancer therapies, and resistance to this programmed cell death facilitates long-lived cancer cells with an accumulation of gene mutations, contributing to uncontrolled cell growth, vascularization and tumor invasion [24,33]. We then focused on the apoptosis targets of 22-(4 py)-JA in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we incubated the vincristine- and daunorubicin-resistant cell lines Nalm-6/BeKa and Nalm-6/LiKa, respectively, with different concentrations of 3. Indeed, DNA fragmentation analysis showed that NAHO27 is also highly effective in inducing apoptosis in these resistant cell lines, which both show a co-resistance to anthracyclines (idarubicin, daunorubicin, doxorubicin, epirubicin), mitoxanthrone, fludarabine, vinca alkaloids (vincristine, vindesine, vinorelbine, vinblastine) and etoposide in vitro 25 ( Fig. 13A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism often results in multidrug resistance (MDR) [ 29 ], which has also been demonstrated for BeKa cells. BeKa cells show a co-resistance to anthracyclines (idarubicin, daunorubicin, doxorubicin, epirubicin), mitoxantrone, fludarabine, vinca alkaloids (vincristine, vindesine, vinorelbine, vinblastine) and etoposide in vitro [ 30 ].…”
Section: Resultsmentioning
confidence: 99%